Vase life of new tropical cut foliage: Cordyline terminalis - Favero, B. T. [UNESP]; Carmello, Q. A.C.; Dias, G. M. (International Society for Horticultural Science (ISHS), 2012)
Cordyline terminalis is a tropical ornamental with high decorative value due its variety of colors and foliar patterns. This ornamental is new in the Brazilian market and has large potential to be exported. The lack of studies on postharvest aspects is a problem for new crops, and the development of good post-production techniques can reduce costs due to loss of unsalable, damaged plants. The present work aimed to characterize the vase life of red and green cultivars of C. terminalis. Conservation techniques, such as pulsing with gibberellic acid (GA3), wax spray, and cold storage for 10 and 20 days at 5, 10, and 13°C were tested. Also, macro- and micronutrients concentration was tracked during the senescence process. In the water-based treatment (control), both cultivars had a vase life of 21 days. Vase life was not influenced by wax spray, GA pulsing, or cold storage for 10 days at 5, 10 or 13°C. In both cultivars, the postharvest techniques used did not improve the vase life on this species. On the other hand, by cold storing the foliage for 20 days in any of the tested temperatures, the vase life was shortened one week, with a total of 14 days longevity compared with all other treatments. Color changes were not correlated with senescence of the foliage. Nutrients did not change during the evaluation period. C. terminalis had a vase life long enough for export, supported by cold storage up to 10 days, which did not shorten the vase life.
Keywords: Cold storage; Gibberellic acid; Postharvest; Wax spray